Pembangunan Gim Edukasi Peraturan Lalu Lintas Kawasan Ganjil Genap di Jakarta Berbasis Android - Randiani, Raudya Enggar; Dirgantara, Harya Bima (Universitas Atma Jaya Yogyakarta, 2020)
Abstract. This study aims to create an educational game for odd-even traffic rules in Jakarta on an android-based platform called